Maritime Information Products from SAR Satellites - Lehner, Susanne (2015)
With 90% of all goods being transported on sea routes an efficient, internationally competitive maritime industry is of high overall economic significance. The global exchange of goods is rising steadily causing an increase of ship traffic. New fuel efficient and safe routes are being discussed. In addition, tourism plays an increasingly important economic role at sea. To increase safety, security and efficiency of shipping and to protect the oceans, global data that provide reliable information about storms and sea state, sea ice cover, environmental pollution and ship locations are of paramount importance. This paper demonstrates the use of the two German high resolution X-band radar satellites TerraSAR-X and TanDEM-X to develop maritime surveillance products, including ship detection and traffic monitoring, oil spill detection or wind and sea-state information. As SAR is capable of all weather imaging, the products are generated independently of clouds and sunlight illumination. As a consequence of climate change the sea ice conditions in the Arctic during the summer months become increasingly attractive for commercial shipping. Timely variable ice conditions require continuous and frequent monitoring to ensure safe, ecofriendly and economic routing of vessels. In this paper we describe the use of X- and C-Band synthetic aperture radar (SAR) earth observation data for the derivation of tactical iceberg information. High resolution SAR data can substantially enhance the situational awareness of the local sea-ice conditions and thus is expected contribute to marine safety as well as to the optimized planning of commercial operations in Arctic waters.